Wisata Luhak Nan Tigo dalam Fotografi Nature - Fernando, Nesta; Kurniadi, Benny; Rahmat, Aziz Fauzi (AHKAM, 2025)
West Sumatra is one of the provinces in the Indonesian region which is famous for its natural beauty, especially natural tourism in Minangkabau which consists of Luhak Nan Tigo, namely Tanah Datar, Luhak Agam, and Luhak Limo Puluah Koto. Luhak Nan Tigo has a natural environment that is still pristine, has many beautiful and interesting tourist attractions through a photographic perspective that will be packaged through nature photography. Through the creation of nature photography works, the artist will display tourist attractions in Luhak Nan Tigo with several categories such as landscape, seascape, skyscape, and cityscape. The artist also uses several angles, namely, low angle, eye level, high angle or aerial. The resulting works amount to 20 photo works. The artist carried out several data collection methods such as literature studies, observations, and interviews, designing the work process, the embodiment of tools and materials in realizing the idea of creation. Through this nature photography, the artist can capture the natural beauty in Luhak Nan Tigo, by capturing the shape and characteristics of the tourist attraction. On the other hand, the creator also wants to make this work as an innovation in nature photography in Luhak Nan Tigo, and it can also be an archive of a tourist attraction in Luhak Nan Tigo over time if it is not managed properly anymore.